DC Electric pump modified as an intelligent actuator - Barbosa Torres, Alex Esteban; Escobar Díaz, Andrés; Vacca González, Harold (Ingeniería Solidaria, 2019)
Introduction: This paper describes the research – developed in 2007 by ORCA and SciBas – that modifies an actuator device (AD) – DC electric pump – making it Smart. Problem: There are currently no intelligent ADs of open architecture with the possibility of being easily manipulated in didactic plants.Objective: To identify and implement circuits to control an AD with signals.Methodology: The AD is developed following the family-standard IEEE 1452: implementing communication interfaces that characterize intelligent transducers connected to systems based on microprocessors, instruments and networks. The integration is made in a configuration platform that displays, records and manipulates AD information through a PC.Results: Obtaining a low-cost system based on Raspberry Pi - as an intelligent core - where the following are integrated: a PSOC 4 microcontroller to interact with the signals of the actuator, a circuit to manage the energy between the pump and the microcontroller, and an integrated signal that goes to a processorOriginality: Modify a DC electric pump -as part of a didactic plant system- to have an intelligent AD architecture. The checking of filling and flow rates indicate advantages over traditional instrumentation: noise immunity, effective isolation of circuits from sources, work sequences, effective storage of actuator information, simple calibration, ease of signal transmission and remote control, and the possibility of intelligent presentations.Limitations: In non-didactic plants it is necessary to extend the research to the industrial sector and increase the quality of the elements.